2005
DOI: 10.1002/lsm.20148
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of low power laser therapy can be mediated by nitric oxide

Abstract: The NO donors added to the cellular suspension before irradiation eliminate the radiation-induced increase in the number of cells attached to the glass matrix, supposedly by way of binding NO to cytochrome c oxidase. NO added to the suspension after irradiation can also inhibit the light-induced signal downstream. Both effects of NO depend on the concentration of the NO donors added. These results indicate that NO can control the irradiation-activated reactions that increase the attachment of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(170 citation statements)
references
References 39 publications
(52 reference statements)
3
152
1
9
Order By: Relevance
“…Possible mechanisms may involve multiple regulatory intra-, inter-or extra-cellular biologic events. Previously, the percentage of HeLa cells attached to the glass surface was found to increase upon irradiating the cell suspension samples with certain wavelengths (Karu et al, 2005). However, the optimal frequency of light treatment was not tested in that study.…”
Section: Discussionmentioning
confidence: 89%
“…Possible mechanisms may involve multiple regulatory intra-, inter-or extra-cellular biologic events. Previously, the percentage of HeLa cells attached to the glass surface was found to increase upon irradiating the cell suspension samples with certain wavelengths (Karu et al, 2005). However, the optimal frequency of light treatment was not tested in that study.…”
Section: Discussionmentioning
confidence: 89%
“…NO is known to cause vasodilatation by triggering the relaxation of smooth muscle associated with endothelium. This vasodilation increases the availability of oxygen to exposed cells and also allows for greater traffic of immune cells into tissue [8,12].…”
Section: Llt-mechanism Of Action On Molecular Levelmentioning
confidence: 99%
“…23.24 In addition, other studies have reported that LLLT directly influences levels of oxidative stress in the skin by modifying antioxidant enzymes and NOS, altering the production of ROS such as peroxynitrite ( -OONO), which is a strong oxidant with the potential to destroy critical cellular components. 17,17,21,22 Some studies also emphasize that there may be a dose and time-dependent relation between LLLT and the production of ROS and free radicals in the skin tissue. 21 -23 According to Karu et al 17.24 and other authors [20][21][22][23] , exposure to LLLT stimulates an extra mitochondrial electrochemical activity and a simultaneous increase in the synthesis of adenosine triphosphate (ATP), in addition to an increase in the intracellular concentration of calcium (Ca +2 ), exerting effects on cellular signaling and increasing the activity of NOS in endothelial cells, which would offer cytoprotection to damage caused by lipid peroxidation induced by LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]17,[20][21][22][23][24] It has also been reported that nitric oxide (NO) produced by activation of the iNOS enzyme in monocytes participates in signaling for deposition of granulation tissue and collagen and for wound contraction (scar formation) via distinct pathways in animal models of wound healing. 3,14,15,17,21,24 Some authors also show biostimulation effects of LLLT on inflammatory cytokines through gene expression modulation of various growth factors such as platelet-derived growth factor (PDGF), transforming growth factor beta (TGF-β), tumor necrosis factor alpha (TNF-α), and interferon gamma (IFN-γ), which are also potentially involved in the healing of skin wounds. 24.25 These regulatory effects of oxidative stress in skin, biomodulation of inflammatory cytokines and growth factors could be related to the histological findings observed in this study, in relation to the isolated treatment with LLLT (He -Ne).…”
Section: Photomicrograph Montage Of Skin Wounds In Micementioning
confidence: 99%
See 1 more Smart Citation